Pengaruh Budaya Organisasi, Kepemimpinan, dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan CV Surya Raya - Laksmi Sito Dwi Irvianti; Rido Justisia Prabowo; Gugi Abdel Permana (Bina Nusantara University, 2012)
This research was conducted on CV Surya Raya which is engaged in car shipping. The aim of this study is to determine the influence of organization culture, leadership, and working motivation partially to employees’ satisfaction in CV Surya Raya. The data was collected by conducting interviews with the company and distributing questionnaires to 67 employees as respondents and then analyzed using linear regression analysis method. From the research results, leadership variable does not have a significant impact on employees' job satisfaction in CV Surya Raya. Whereas, the motivation variable has greater influence on job satisfaction of CV Surya Raya employees compared to the organization's culture.